ANJURAN PERSIAPAN BERWISATA PADA PENDERITA GAGAL JANTUNG: LITERATURE REVIEW - Haifah, Nur; Kamayani, Made Oka Ari; Manangkot, Meril Valentine (Coping: Community of Publishing in Nursing; Vol 11 No 6 (2023): Desember 2023, 2024)
International travel is seen as medical tourism, in that the client (patient) leaves his or her home country for medical, health, or treatment purposes, being an important form of tourism in countries that have invested in healthcare. Heart-related illnesses generally contribute to in-flight medical emergencies; hence a good knowledge of the relationship between CVD (cardiovascular disease) and international travel is essential. Heart disease can be associated with clinical symptoms such as dyspnoea, fatigue and cause exercise intolerance. As a result, patients with heart disease may experience some degree of limitation in social and daily life. Most heart disease patients experience impaired physical and functional capacities, which can affect the patient's quality of life. So for people with heart disease need to make preparations before traveling such as needing to prepare more stable health conditions, medicines, vaccines, and travel insurance to avoid things that are not desirable .